2015
DOI: 10.34024/rnc.2015.v23.7980
|View full text |Cite
|
Sign up to set email alerts
|

Risco para síndrome da apneia obstrutiva do sono e sua relação com consumo alimentar

Abstract: Objetivo. Verificar a associação de risco para Síndrome da Apneia Obstrutiva do Sono (SAOS) com o consumo de gorduras e fibras. Mé­todo. Estudo descritivo realizado na Sociedade Beneficente de Senho­ras Hospital Sírio Libanês (HSL). Participaram 1030 indivíduos que foram avaliados quanto idade, sexo, peso, estatura e Índice de Massa Corporal (IMC). Para investigar a ingestão alimentar foi aplicado o Questionário de Freqüência Alimentar (QFA) e para classificar o risco para SAOS foi aplicado Questionário de Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
3
1
4
Order By: Relevance
“…An original study by Saygin et al (2016) 16 with 337 university medical students from Turkey identified that only 5 (1.5%) were diagnosed with higher OSA risk. According to Khassawneh et al (2018) 17 this percentage reached 5.4% on higher education students from Jordan, whereas it was found by Carvalho et al (2015) 19 that this percentage reached 23,13% on Sirian-Lebanese Hospital from southest Brazil, in our study OSA risk was 12.2% on the population studied.…”
Section: Discussioncontrasting
confidence: 64%
“…An original study by Saygin et al (2016) 16 with 337 university medical students from Turkey identified that only 5 (1.5%) were diagnosed with higher OSA risk. According to Khassawneh et al (2018) 17 this percentage reached 5.4% on higher education students from Jordan, whereas it was found by Carvalho et al (2015) 19 that this percentage reached 23,13% on Sirian-Lebanese Hospital from southest Brazil, in our study OSA risk was 12.2% on the population studied.…”
Section: Discussioncontrasting
confidence: 64%
“…A previous study demonstrated the association reason of chance of 13.95% (p<0.001) for the occurrence of sleep obstructive apnea syndrome with high risk for obese patients, in comparison with overweight (7.02%) and eutrophic (2.14%) ones, and 25% of the individuals presented high consumption of fat (Carvalho et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…However, a generic interpretation of the findings in this study points that greater concentration of fat, greater BMI and low body water concentration (tissue dehydration) negatively impacted sleep quality, specifically on sleep disturbances, customary sleep efficiency and sleep duration. Although no studies, with similar methodological profile, were found demonstrating such correlations, other studies demonstrated general causal relation between increased body fat and impaired sleep (Carvalho et al 2015;Lustosa et al 2016;Monçale Neto et al 2016;Ruthes et al 2017;Zimberg et al 2017;Andrade et al 2018;Cardoso and Chagas 2019;Heath et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age is the principal risk factor associated with OSA [4]. Also, sleep disorders are correlated with decreased fiber intake, increased carbohydrate intake, and increased fat consumption [5]. Obese patients are more likely to have a positive OSA diagnosis, mainly due to the increased fat deposition in the neck region.…”
Section: Rbfex Introductionmentioning
confidence: 99%